2019
DOI: 10.1111/cid.12752
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and radiographic outcomes of Schneiderian membrane perforation without repair in sinus elevation surgery

Abstract: Background The aim of this comparative study was to evaluate the clinical outcome of nonrepair of the perforated maxillary sinus membrane compared to the nonperforated cases. Materials and Methods A retrospective comparative study was performed by identifying all lateral window sinus augmentation procedures, which were done during a defined period. Demographic data, systemic diseases, and smoking habits of patients were recorded. Thickness of the Schneiderian membrane and the amount of residual bone before sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 27 publications
2
62
0
6
Order By: Relevance
“…The mean Schneiderian membrane perforation rate was 30.6% (489 perforations). Different treatments were used to resolve the perforations, including post-perforation clot formation [ 4 ], suturing [ 47 ], use of collagen membranes [ 16 ], Platelet-rich fibrin (PRF) [ 19 ], hemostatic agents [ 49 ], laminar bone [ 50 ], and block grafts [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean Schneiderian membrane perforation rate was 30.6% (489 perforations). Different treatments were used to resolve the perforations, including post-perforation clot formation [ 4 ], suturing [ 47 ], use of collagen membranes [ 16 ], Platelet-rich fibrin (PRF) [ 19 ], hemostatic agents [ 49 ], laminar bone [ 50 ], and block grafts [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most common post-operative complication found in sinuses with perforated membranes was the appearance of signs of infection. Park et al [ 4 ] reported a greater number of postoperative complications in patients with perforated membranes including bleeding from the perforation site, leakage of cystic fluid or purulent exudate, displacement of the graft into the sinus, nasal bleeding, and facial swelling. Other complications with lower incidence such as pain or tenderness in the treated area were also reported [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hauman et al [ 38 ] stated that the sinus mucosa, complete with cilia, regenerates about five months after its surgical removal and therefore the invasion of the maxillary sinus does not appear to cause a permanent alteration of either the sinus membrane or its physiological function and the sinusitis will be resolved once adequate ventilation is restored. It is interesting to note that a recent study has shown that the perforation without repair of the sinus membrane during sinus lift procedure, did not affect the result of bone grafting and implant survival rate [ 39 ]. Few studies have focused on apicectomies of posterior teeth whose success rate ranged from 44 to 88% [ 21 , 40 ] depending on the surgical technique and on the differences in the postoperative evaluation criteria.…”
Section: Introductionmentioning
confidence: 99%